Fruit quality of Brazilian genotypes of feijoa at harvest and after storage - Amarante, Cassandro Vidal Talamini do; Souza, Alexandra Goede de; Benincá, Thalita Dal Toé; Steffens, Cristiano André (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the physicochemical attributes and vitamin C contents of fruits of five Brazilian genotypes of feijoa (Acca sellowiana), at harvest and after cold storage. The Alcântara, Mattos, Helena, and Nonante cultivars, as well as accession 2316, were studied. The assessed attributes were: fresh mass loss, titratable acidity, soluble solids contents, soluble solids contents/titratable acidity ratio, pH, skin and flesh color, texture, and vitamin C contents (skin and flesh). After storage, there were reductions of 2.9% in soluble solids contents, of 32.2% in titratable acidity, and of approximately 85% in texture attributes, besides increases of 36.3% in the soluble solids contents/titratable acidity ratio and of 21.7% in the pH of fruits. The vitamin C content in the skin was higher than that in the flesh, and increased in both skin and flesh after storage. 'Alcântara' fruits have the highest contents of vitamin C in the skin and flesh. Fruits of 'Nonante' and 'Mattos' show better preservation of the texture attributes, and fruits of 'Nonante', the lowest levels of flesh browning during storage.